Axiology of Islamic Education Management in Education Quality Development - Azis, Taufiq Nur; Susanto, Susanto (Jurnal Inovatif Manajemen Pendidikan Islam, 2026)
Islamic education management possesses unique characteristics that distinguish it from national education management due to its roots in religious values. However, in practice, Islamic educational institutions face significant challenges in integrating the essence of Islamic teachings into policies, curriculum, and daily decision-making amidst changing times. This study employs a qualitative approach with a descriptive-analytical method. Data collection was conducted through library research by exploring various primary and secondary literature sources, such as books, scientific journals, and other relevant publications related to axiology, Islamic philosophy, and educational management. The research findings indicate that the axiology of Islamic education management encompasses two value tendencies: theoretical values (the systematization of knowledge based on Islamic aesthetics and ethics) and practical values (the internalization of Islamic cultural values). The primary axiological values include: 1) I’tiqodiyah values (faith), 2) Khuluqiyah values (prophetic ethics: shiddiq, amanah, tabligh, fathanah), 3) Amaliyah values (mahdhah and ghairu mahdhah worship), and 4) Al-Dharuriyat al-Sittah values (the protection of religion, life, intellect, lineage, property, and environment). Axiology in Islamic education management serves as the foundation for shaping ethics and character. The application of prophetic values and the principle of public interest (al-Daruriyat al-Sittah) ensures that educational management pursues not only worldly (academic) success but also ukhrawi (moral) success, thereby creating education that is relevant, high-quality, and beneficial to human dignity.